Unforeseen succession: Identity change amongst lateral entrants in family firms - Pia Doris Morrow (Junior Management Science (JUMS), 2024)
Due to the increasing globalization of today's world, descendants of family firms are often drawn to the unlimited opportunities outside their premises and no longer see their future workplace or the core of their identity within the family organization. However, this can lead to a rude awakening if so-called unforeseen events, which can range from death or illness of a family member to intra-family conflicts, changes in the business model and even financial problems, arise. This thesis examines the effects of such unexpected successions on the identity of lateral entrants in family firms and presents a roadmap with practical and theoretical action implications for unplanned successors during the pre-, initial, and post-succession phase. The analysis of qualitative data from interviews with lateral entrants and experts revealed overlaps in identity constructs and experiences. Before the occurrence of an unforeseen event, lateral entrants already displayed entrepreneurial traits and a willingness to take risks but lacked connection to the family firm and interest in succession. During the initial succession phase, they prioritized rationality, efficient teams, and immediate action over emotional processing. After an average of three years, lateral entrants became confident family entrepreneurs. Furthermore, unforeseen successors showed great interest in arranging their own succession at an early stage in order to pass on what they had learned and counteract crisis situations preventively. In general, the interviewed candidates demonstrated a continuous process of developing their own successor identity, which did not develop disruptively but rather steadily and was characterized by specific milestones shown in the successor roadmap of this thesis.
Keywords: 330; crisis management; family firm succession; Gioia methodology; social identity theory; unforeseen succession